Reporting and Publishing Research in the Biomedical Sciences (Springer Singapore, 2018)
This book eases the task of converting research work into a manuscript, and covers the recent developments in publishing that often stump budding researchers. Few researchers in the biomedical sciences are trained in the essential skills of reporting their results, and they seek help in writing a paper that will be acceptable for publication in the 'right' journal, and in presenting their results 'effectively' at a meeting. As well as covering the basic aspects of preparing manuscripts for publication, the book discusses best practices and issues relating to the publication of biomedical research, including topics such as peer-review, authorship, plagiarism, conflicts of interest, publication misconduct, electronic publishing and open-access journals. With more than two decades of experience in conducting workshops on writing scientific papers, the editors have brought together the expertise of 29 authors from seven countries to produce this one-stop guide to publishing research in biomedical sciences. This book is intended for young researchers who are beginning their careers and wish to hone their skills and understand the rigors of research writing and publishing.